Process optimization of tetracycline degradation by H2O2 - Ooi, Burker Ooi; Buono, Pietro; Viknesh, Sonia; Lanzalaco, Aimin; Sirés, Christian (Journal of Functional Materials and Applied Engineering, 2024)
Antibiotic abuse has evolved into a serious and pressing global concern. The misuse of antibiotics has precipitated a range of problems, particularly posing significant threats to aquatic environments. Antibiotic contamination in water bodies leads to the persistence of antibiotics and their metabolites, causing toxic influences and harm to aquatic organisms, damaging genetic and cellular structures, and contributing to the escalation of bacterial resistance. Consequently, addressing antibiotic pollution in aquatic systems is paramount for safeguarding water quality and ecological balance. For edta-Fe⁰/H2O2 system, using 0.3 g/L edta-Fe⁰ and 60mm H2O2, under the condition of pH 6.5, TC can be influenceively removed within 60 minutes, and the removal rate can reach 90.2%. In contrast, the unmodified FE⁰/H2O2 system can only remove 23.9% of TC. In addition, edta-Fe⁰/H2O2 system has good removal influence on different types of pollutants, and has good recycling capacity and adaptability, which is suitable for actual wastewater treatment. Through quenching test EPR, the catalytic mechanism of edta-Fe⁰ for H2O2 was confirmed by the studies of shell separated nano particle enhanced Raman spectroscopy (shiners) and DFT calculation, and · oh was found to be the main reaction species. Therefore, enhancing the decomposition of H2O2 to produce · OH plays an important role in enhancing the degradation of pollutants. H2O2 can be decomposed in two ways, namely, the breaking of peroxide bond to form · OH or the breaking of O-H bond to form *ooh. Then, the peroxide bond breaks and · OH is produced by impact. EDTA-Fe⁰ modification can enhance these decomposition pathways, so as to produce more · OH and improve the catalytic activity. The reaction path and intermediate products of edta-Fe⁰/H2O2 were detected by LC-MS. toxicity evaluation showed that the toxicity of TC was reduced. In addition, the structure, in particular functional groups, of APCA on performance of APCA-Fe⁰ system was explored. The amount of carboxyl group (-COOH) is very important to improve the performance, and amino (-NH2) group content also plays a role in the performance of APCA-Fe⁰ system. When catalyst contains more COOH and NH2 groups, the reaction activity and antibiotic elimination rate will be improved. The synergistic influence of NH2 and COOH groups can promote electron transfer and accelerate Fe (II) liberation, thus enhancing the performance and TC removal. Therefore, in design and preparation of APCA-Fe⁰, selecting the appropriate APCA can enhance permeability of the catalyst, so as to improve its performance and application value.